**Q: Solve for x:**

2^{2x} + 2^{x+2} – 12 = 0

A: The first thing we need to notice (from practice and experience) is that we can re-write this like so using our knowledge / rules of exponents:

(2^{x})^{2} + 2^{2}*2^{x} – 12 = 0

Now simplify a little:

(2^{x})^{2} + 4*2^{x} – 12 = 0

So, look at this in a new light. What if we substitute each 2^{x} with y?

(**2**^{x})^{2} + 4***2**^{x} – 12 = 0 turns into y^{2} + 4*y – 12 = 0

(this isn’t necessary, but is helpful for visualization)

We see this is in the form of a quadratic and can be factored:

(y + 6)(y – 2) = 0

So, y = -6 or y = 2

Remember, y was a substitution for 2^{x}. So, we really have:

2^{x} = -6 or 2^{x} = 2

Solve each equation separately. Let’s start with:

Continue reading Solving Exponential Equations by Factoring

### Like this:

Like Loading...